Role Of Homestay In Reviving Tourism In Shimla ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2022)
Background: At seasonal tourist destinations like Shimla, rooms may remain vacant and unoccupied during lean peri ods. To add on, pandemic has already shut many small lodging facilities. Objective: The aim of this study is to improve  our understanding of how homestay activities can contribute to revitalize sustainable tourism trends in Shimla, the study  assumes particular importance in a period of economic crisis characterized by post covid trauma. Methodology: A  survey was conducted in Shimla after first wave of corona virus from September 20 to December 20 as soon as the travel  restrictions were uplifted. The travel and accommodation preferences of tourists were observed and found to be shifting  towards less frequently visited places avoiding mass tourism. To highlight the role of homestays in reviving these tourism  trends, three objectives were identified. Two separate questionnaires were developed to get the quantitative and qualitative data for this research. The data was tabulated and evaluated using SPSS tool. Results: The findings presented  the analysed profile of the potential homestay operators as well as visitors seeking homestay tourism. It also reports the  motivations, expectation and experience of the tourists regarding various aspects of homestay. Conclusion: Homestays  can act as potential vital tool in reviving tourism.
Keywords: Homestay; Covid; Sustainable Tourism; Coronavirus